Reconstitution of human microglia and resident T cells in the brain of humanized DRAGA mice - Ghosh Roy, Sounak; Karim, Ahmad F.; Brumeanu, Teodor-D.; Casares, Sofia A. (Frontiers in Cellular and Infection Microbiology, 2024)
Humanized mouse models are valuable tools for investigating the human immune system in response to infection and injury. We have previously described the human immune system (HIS)-DRAGA mice (HLA-A2.HLA-DR4.Rag1KO.IL-2RgKO.NOD) generated by infusion of Human Leukocyte Antigen (HLA)-matched, human hematopoietic stem cells from umbilical cord blood. By reconstituting human cells, the HIS-DRAGA mouse model has been utilized as a “surrogate in vivo human model” for infectious diseases such as Human Immunodeficiency Virus (HIV), Influenza, Coronavirus Disease 2019 (COVID-19), scrub typhus, and malaria. This humanized mouse model bypasses ethical concerns about the use of fetal tissues for the humanization of laboratory animals. Here in, we demonstrate the presence of human microglia and T cells in the brain of HIS-DRAGA mice. Microglia are brain-resident macrophages that play pivotal roles against pathogens and cerebral damage, whereas the brain-resident T cells provide surveillance and defense against infections. Our findings suggest that the HIS-DRAGA mouse model offers unique advantages for studying the functions of human microglia and T cells in the brain during infections, degenerative disorders, tumors, and trauma, as well as for testing therapeutics in these pathological conditions.